Phase noise in RF and microwave amplifiers - Boudot, R.; Rubiola, E. (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2012)
Understanding amplifier phase noise is a critical issue in many fields of engineering and physics, such as oscillators, frequency synthesis, telecommunication, radar, and spectroscopy; in the emerging domain of microwave photonics; and in exotic fields, such as radio astronomy, particle accelerators, etc. Focusing on the two main types of base noise in amplifiers, white and flicker, the power spectral density of the random phase φ(t) is S φ (f) = b 0 + b -1 /f. White phase noise results from adding white noise to the RF spectrum in the carrier region. For a given RF noise level, b 0 is proportional to the reciprocal of the carrier power P 0 . By contrast, flicker results from a near-dc 1/f noise-present in all electronic devices-which modulates the carrier through some parametric effect in the semiconductor. Thus, b -1 is a parameter of the amplifier, constant in a wide range of P 0 . The consequences are the following: Connecting m equal amplifiers in parallel, b -1 is 1/m times that of one device. Cascading m equal amplifiers, b -1 is m times that of one amplifier. Recirculating the signal in an amplifier so that the gain increases by a power of m (a factor of m in decibels) as a result of positive feedback (regeneration), we find that b -1 is m 2 times that of the amplifier alone. The feedforward amplifier exhibits extremely low b -1 because the carrier is ideally nulled at the input of its internal error amplifier. Starting with an extensive review of the literature, this article introduces a system-oriented model which describes the phase flickering. Several amplifier architectures (cascaded, parallel, etc.) are analyzed systematically, deriving the phase noise from the general model. There follow numerous measurements of amplifiers using different technologies, including some old samples, and in a wide frequency range (HF to microwaves), which validate the theory. In turn, theory and results provide design guidelines and give suggestions for CAD and simulation. To conclude, this article is intended as a tutorial, a review, and a systematic treatise on the subject, supported by extensive experiments.